Exploring consumer exposure pathways and patterns of use for chemicals in the environment. (2015) - Dionisio, Kathie L.; Frame, Alicia M.; Goldsmith, Michael-Rock; Wambaugh, John F.; Liddell, Alan; Cathey, Tommy; Smith, Doris; Vail, James; Ernstoff, Alexi S.; Fantke, Peter; Jolliet, Olivier; Judson, Richard S.
Highlights: To assign use-related information to chemicals to help prioritize which will be given more scrutiny relative to human exposure potential. Categorical chemical use and functional information are presented through the Chemical/Product Categories Database (CPCat). CPCat contains information on >43, 000 unique chemicals mapped to ∼800 terms categorizing their usage or function. The CPCat database is useful for modeling and prioritizing human chemical exposures. Abstract: Humans are exposed to thousands of chemicals in the workplace, home, and via air, water, food, and soil. A major challenge in estimating chemical exposures is to understand which chemicals are present in these media and microenvironments. Here we describe the Chemical/Product Categories Database (CPCat), a new, publically available (http://actor.epa.gov/cpcat ) database of information on chemicals mapped to "use categories" describing the usage or function of the chemical. CPCat was created by combining multiple and diverse sources of data on consumer- and industrial-process based chemical uses from regulatory agencies, manufacturers, and retailers in various countries. The database uses a controlled vocabulary of 833 terms and a novel nomenclature to capture and streamline descriptors of chemical use for 43, 596 chemicals from the various sources. Examples of potential applications of CPCat are provided, including identifying chemicals to which children may be exposed and to support prioritization of chemicals for toxicity screening. CPCat is expected to be a valuable resource for regulators, risk assessors, and exposure scientists to identify potential sources of human exposures and exposure pathways, particularly for use in high-throughput chemical exposure assessment.